2021
DOI: 10.1039/d1ra00865j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and tunable visible-light-catalytic synthesis of 2,5-diformylfuran using HBr and molecular oxygen

Abstract: HBr is a very cheap and efficient bifunctional catalyst for the synthesis of DFF from the photooxidation of HMF by O2 and from the cascade conversion of fructose via a one-step or especially the two-step protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In fact, Hu et al demonstrated that by using HBr in DMSO in a two-step process 80% DFF yield was achieved. 53 Bromide and the photogenerated O 2…”
Section: Fabio Aricòmentioning
confidence: 99%
“…In fact, Hu et al demonstrated that by using HBr in DMSO in a two-step process 80% DFF yield was achieved. 53 Bromide and the photogenerated O 2…”
Section: Fabio Aricòmentioning
confidence: 99%
“…Interestingly, a further study by Hu et al confirmed that the cheap HBr acid could even catalyze this reaction under visible light in O 2 and water. 80 However, a higher temperature (80 °C) was required. 91% conversion of HMF and 89% selectivity of DFF were obtained in DMSO.…”
Section: Photocatalytic Oxidation Of Hmf To Dffmentioning
confidence: 99%